The Prohibition of Trading, Conducting Business, and Exacting Usury According to the Current Codified Discipline (can. 286 CIC/83; can. 385 § 2 CCEO) and Selected Fourth-Century Catholic Church Jurisprudence - Kretkowski, Alan (Prawo Kanoniczne, 2026)
In the article, canonical prohibitions of trading, conducting business activity, and charging usury in Catholic canon law of the twentieth century (CIC/17; CIC/83; motu proprio Cleri sanctitati; CCEO) and in selected fourth-century enactments of the First Council of Nicaea, selected synods, together with the Apostolic Canons are analysed. In the first part can. 142, together with can. 1543 CIC/17 and can. 83 CS are examined. In the second part can. 286 CIC/83and can. 385 § 2 CCEO are analysed by identifying the addressees of these norms, clarifying key Latin terminology, outlining the applicable sanctions, indicating the prescriptive periods for penal action, and specifying the canonical impediments they create, namely, to receiving sacred orders and to the exercise of orders illicitly received. In the third part fourth-century conciliar-synodal rulings and canons are surveyed by providing information about the source of their adoption; discussing their decisions and comparing them to contemporary regulations. In the text are mentioned: can. 19 and 20 of the Synod of Elvira (ca. 306); can. 13 of the Synod of Arles (314); can. 17 of the First Council of Nicaea (325); can. 6, 8, 9, and 13 of the Synod of Carthage (ca. 348); can. 6 and 44 of the Apostolic Canons (ca. late fourth century). In the conclusion the principal findings of the article are synthesized.